320-Row wide volume CT significantly reduces density heterogeneity observed in the descending aorta: Comparisons with 64-row helical CT - Yamashiro, Tsuneo; Miyara, Tetsuhiro; Honda, Osamu; Kamiya, Ayano; Tanaka, Yuko; Murayama, Sadayuki (Computerized medical imaging and graphics, 2014)
The aim of this study was to compare density heterogeneity on wide volume (WV) scans with that on helical CT scans. 22 subjects underwent chest CT using 320-WV and 64-helical modes. Density heterogeneity of the descending aorta was evaluated quantitatively and qualitatively. At qualitative assessment, the heterogeneity was judged to be smaller on WV scans than on helical scans (p<0.0001). Mean changes in aortic density between two contiguous slices were 1.64HU (3.40%) on WV scans and 2.29HU (5.19%) on helical scans (p<0.0001). CT density of thoracic organs is more homogeneous and reliable on WV scans than on helical scans.